National Culture, Transaction Costs, and the Choice Between Joint Venture and Wholly Owned Subsidiary - Makino, Shige; Neupert, Kent E. (Journal of International Business Studies, 2000)
Transaction cost theory posits that culture plays a limited role in the choice between JV and WOS. In contrast, research suggests that firms’ preferred level of ownership in their foreign subsidiaries is influenced primarily by cultural traits. This study provides additional evidence in this ongoing debate by replicating Hennart's transaction cost model of entry mode choice in two different national contexts: Japanese firms investing in the U.S. and the U.S. firms investing in Japan. The results suggest that the transaction cost explanation for the ownership choice holds in the both national contexts. Yet, the propensity to choose JV or WOS significantly varied between Japanese and the U.S. firms.